A massive pelvic mucocele presenting as a cystic sacral mass. Issue 11 (November 2015) - Boone, Christine; Rory Goodwin, C.; Crane, Genevieve; Pendleton, James; Sciubba, Daniel
Highlights First report of an extra-appendiceal mucinous cystadenoma involving the sacral spine. Previous inflammatory bowel disease and/or extensive pelvic/abdominal surgery may be associated with mucocele. Definitive preoperative diagnosis is not always possible. Propensity to recur necessitates post-operative follow-up.